Decolorization of azo dyes with Klebsiella Pneumoniae under high saline conditions - Gopi, Tejasri (Nanyang Technological University, 2021)
Textile industries generate colored wastewater after the dyeing process and the color is still visible even at low concentrations such as ~10 ppm. If disposed untreated, they are toxic to the aquatic environment and negatively impact the soil fertility. Bioremediation was considered as the cost-effective and environmentally benign alternative over the past two decades. But dyes are large and heavy, structurally complex molecules and hence are not readily degradable. In the typical aerobic wastewater treatment systems, they either got trapped in the sludge or exited untreated requiring downstream processing while anaerobic biological treatment resulted in the formation of aromatic amines that are more toxic, persistent, and carcinogenic as compared to the parent dyes. Besides this, high dosages of salts such as chlorides and sulfates that are another consequence of dyeing often hinder the biodegradation of the dyes. To address these problems, this thesis work focuses on isolating a halotolerant facultative anaerobe that decolorizes and degrades industrially important sulfonated azo dyes in oxygen abundant conditions under the influence of sulfates and chlorides. Further, it involves tracking the fate of the by-products generated during decolorization.